Evaluation of spine disorders using high contrast imaging of the cartilaginous endplate - Athertya, Jiyo S.; Statum, Sheronda; Chen, Xiaojun; Du, Kevin; Shin, Soo Hyun; Jerban, Saeed; Chung, Christine B.; Chang, Eric Y.; Ma, Yajun (Frontiers in Physiology, 2024)
Introduction: Many spine disorders are caused by disc degeneration or endplate defects. Because nutrients entering the avascular disc are channeled through the cartilaginous endplate (CEP), structural and compositional changes in the CEP may block this solute channel, thereby hindering disc cell function. Therefore, imaging the CEP region is important to improve the diagnostic accuracy of spine disorders.Methods: A clinically available T1-weighted and fat-suppressed spoiled gradient recalled-echo (FS-SPGR) sequence was optimized for high-contrast CEP imaging, which utilizes the short T1 property of the CEP. The FS-SPGR scans with and without breath-hold were performed for comparison on healthy subjects. Then, the FS-SPGR sequence which produced optimal image quality was employed for patient scans. In this study, seven asymptomatic volunteers and eight patients with lower back pain were recruited and scanned on a 3T whole-body MRI scanner. Clinical T2-weighted fast spin-echo (T2w-FSE) and T1-weighted FSE (T1w-FSE) sequences were also scanned for comparison.Results: For the asymptomatic volunteers, the FS-SPGR scans under free breathing conditions with NEX=4 showed much higher contrast-to-noise ratio values between the CEP and bone marrow fat (BMF) (CNRCEP-BMF) (i.e., 7.8±1.6) and between the CEP and nucleus pulposus (NP)) (CNRCEP-NP) (i.e., 6.1±1.2) compared to free breathing with NEX=1 (CNRCEP-BMF: 4.0±1.1 and CNRCEP-NP: 2.5±0.9) and breath-hold condition with NEX=1 (CNRCEP-BMF: 4.2±1.3 and CNRCEP-NP: 2.8±1.3). The CEP regions showed bright linear signals with high contrast in the T1-weighted FS-SPGR images in the controls, while irregularities of the CEP were found in the patients. Discussion: We have developed a T1-weighted 3D FS-SPGR sequence to image the CEP that is readily translatable to clinical settings. The proposed sequence can be used to highlight the CEP region and shows promise for the detection of intervertebral disc abnormalities.